2017
DOI: 10.3892/etm.2017.5283
|View full text |Cite
|
Sign up to set email alerts
|

Rhein lysinate protects renal function in diabetic nephropathy of KK/HlJ mice

Abstract: The purpose of the present study was to assess the protective effects of rhein lysinate (RHL) in a KK/HlJ mouse model of diabetic nephropathy (DN) and to explore its mechanism of action. A total of 4 groups were established: C57BL/J control, the KK/HlJ model and 25 and 50 mg/kg/day RHL-treated KK/HlJ groups. The KK/HlJ mouse model of DN was established by streptozotocin injection, followed by maintenance on a specific diet. The albumin-to-creatinine ratio (ACR) was determined at 5 weeks and at 16 weeks, the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Oxidative stress is of great effect for the occurrence and development of DN, while SOD and MDA are common indicators of oxidative stress. Lin et al (2017) indicated that rhein increased the level of SOD and decreased the level of MDA in kidney tissues of KK/HlJ mice. (Li and Zhen, 2017) found that medium-dose rhein had stronger effect on ameliorating SOD and MDA than low-dose.…”
Section: Implication For Further Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Oxidative stress is of great effect for the occurrence and development of DN, while SOD and MDA are common indicators of oxidative stress. Lin et al (2017) indicated that rhein increased the level of SOD and decreased the level of MDA in kidney tissues of KK/HlJ mice. (Li and Zhen, 2017) found that medium-dose rhein had stronger effect on ameliorating SOD and MDA than low-dose.…”
Section: Implication For Further Studiesmentioning
confidence: 97%
“…There was significant association of rhein with TGF-β 1 (n = 34, SMD = -1.49, 95%CI [-2.28, -0.71], P = 0.0002; Heterogeneity: Chi² = 0.00, P = 0.99, I² = 0% Figure 10). There were no data on blood glucose, MDA and SOD in these studies listed as follows: Duan et al, 2015;Gao et al, 2010;Wu, 2015;Lin et al, 2017, but blood glucose, MDA and SOD were presented graphically. These studies were not included in quantitative analyses, but all reported that rhein had significant effects on blood glucose (P < 0.05), MDA (P < 0.05) and SOD (P < 0.05).…”
Section: Tgf-βmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, at least part of the nephroprotective effect of BMP7 administration in diverse models of kidney fibrosis, including streptozotocin-induced DKD, was mediated by restoring TET3 mRNA expression and protein levels suppressed by TGF-β1, resulting in TET3-mediated restoration of the expression of the antifibrotic gene Rasal1. In this regard, aberrant Rasal1 methylation and hydroxymethylation were corrected by BMP7 [82] which is a nephroprotective compound for different models of CKD, including diabetic nephropathy (DN) [83]. A potential mechanism of kidney protection may be the recovery of Klotho expression by reducing the characteristic Klotho promoter hypermethylation, which is observed in CKD [84].…”
Section: Dna Methylation In Diabetic Kidney Diseasementioning
confidence: 99%
“…Modern pharmacology studies have showed that RH could obviously restrains the proliferation of glomerular mesangial cells and hypertrophy of glomerulus, the production and accumulation of extracellular matrix. In addition, it suppresses mRNA transcription, thrombospondin-1 (TSP-1), and transforming growth factor-beta1 (TGF-β1) expression in renal tubular epithelial cells in order to reduce urinary protein and renal fibrosis, ameliorate renal function to protect against CGN deterioration mediated by regulating MAPK signaling pathway, PI3K-AKT signaling pathway, TGF-β signaling pathway, Wnt signaling pathway, VEGF signaling pathway, and others ( Zheng et al., 2008 ; He et al., 2011 ; Zeng et al., 2014 ; Lian et al., 2014 ; Lin et al., 2017 ; Wang et al., 2018 ). It is easy to see that RH protects against CGN in multi-target and multi-level way.…”
Section: Introductionmentioning
confidence: 99%